Noble‐Metal‐Free Photocatalytic H2 Generation: Active and Inactive 'Black' TiO2 Nanotubes and Synergistic Effects. Issue 39 (9th August 2016) - Liu, Ning; Schneider, Christopher; Freitag, Detlef; Zolnhofer, Eva M.; Meyer, Karsten; Schmuki, Patrik
Abstract: Over the past five years a number of different synthesis approaches has been reported to obtain so‐called 'black' titania. One of the outstanding features of the material is that certain synthesis processes lead to the formation of an intrinsic co‐catalytic center and thus enable noble‐metal free photocatalytic H2 ‐generation. In the present work, using TiO2 nanotube layers, we compare three common 'blackening' approaches, namely i) the original high‐pressure hydrogenation (HPT‐H2 ), ii) a classic high temperature reduction in Ar, and iii) an electrochemical (cathodic) reduction. We demonstrate that except for high pressure hydrogenation also cathodic reduction leads to an activation of TiO2 ‐ that is, it exhibits noble‐metal‐free photocatalytic H2 generation. Moreover, we show that a combination of cathodic reduction/high pressure hydrogenation leads to a synergistic effect, that is, a significant enhancement of the combined co‐catalytic activity. Abstract : Different forms of 'black' TiO2 nanotubes have been demonstrated to exhibit noble‐metal‐free photocatalytic H2 generation (see figure). In addition, it has been shown that, except for high‐pressure hydrogenation, also cathodic reduction leads to an activation of TiO2 and, moreover, provides a synergistic effect, that is, a significant enhancement of the combined overall co‐catalytic activity for H2 evolution.